Quadratic Surfaces: Substitute (a,b,c) into z=y^2-x^2

In summary, quadratic surfaces are three-dimensional shapes that can be represented by a quadratic equation in three variables. They have various forms and can be used to model real-world phenomena. To substitute values into the equation, simply replace the variables with their corresponding values. The equation z=y^2-x^2 represents a hyperbolic paraboloid and is commonly used in mathematics and physics. To graph a quadratic surface, you can use a three-dimensional graphing tool or plot points manually. Some real-life applications of quadratic surfaces include modeling satellite dishes, predicting projectile trajectories, and designing roller coasters.
  • #1
Fernando Rios
96
10
Homework Statement
Show that if the point (a,b,c) lies on the hyperbolic paraboloid z=y^2-x^2, then the lines with parametric equations x=a+t, y=b+t, z=c+2(b-a)t and x=a+t, y=b-t, z=c-2(b+a)t both lie enterily on this paraboloid.
Relevant Equations
z=y^2-x^2
x=a+t, y=b+t, z=c+2(b-a)t and x=a+t, y=b-t, z=c-2(b+a)t
Substitute (a,b,c) into z=y^2-x^2:
c=b^2-a^2

Substitute the parametric equations of L1 into the equation of the hyperbolic paraboloid in order to find points of intersection:
z=y^2-x^2
c+2(b-a)t=(b+t)^2-(a+t)^2=b^2-a^2+(b-a)t
c=b^2-a^2
 
Physics news on Phys.org
  • #2
Fernando Rios said:
Homework Statement:: Show that if the point (a,b,c) lies on the hyperbolic paraboloid z=y^2-x^2, then the lines with parametric equations x=a+t, y=b+t, z=c+2(b-a)t and x=a+t, y=b-t, z=c-2(b+a)t both lie enterily on this paraboloid.
Relevant Equations:: z=y^2-x^2
x=a+t, y=b+t, z=c+2(b-a)t and x=a+t, y=b-t, z=c-2(b+a)t

Substitute (a,b,c) into z=y^2-x^2:
c=b^2-a^2

Substitute the parametric equations of L1 into the equation of the hyperbolic paraboloid in order to find points of intersection:
z=y^2-x^2
c+2(b-a)t=(b+t)^2-(a+t)^2=b^2-a^2+(b-a)t
c=b^2-a^2
Looks good, except that you should write it backward.

We need to show that all points ##\begin{bmatrix}
x\\y\\z \end{bmatrix}=\begin{bmatrix}a\\b\\c\end{bmatrix}+t\cdot \begin{bmatrix}
1\\ \pm 1\\ \pm 2b -2a\end{bmatrix}## obey the rule ##y^2-x^2=z.##
\begin{align*}
y^2-x^2&=(b\pm t)^2-(a+t)^2=b^2 \pm 2bt +t^2- a^2-2at-t^2\\
&=c + t(\pm 2b-2a)= c \pm 2(b\mp a)t=z
\end{align*}
Of course, you can handle both cases separately if you like that better.
 
  • #3
I think it looks good except that you should state more clearly what some steps are doing.
Fernando Rios said:
Homework Statement:: Show that if the point (a,b,c) lies on the hyperbolic paraboloid z=y^2-x^2, then the lines with parametric equations x=a+t, y=b+t, z=c+2(b-a)t and x=a+t, y=b-t, z=c-2(b+a)t both lie enterily on this paraboloid.
Relevant Equations:: z=y^2-x^2
x=a+t, y=b+t, z=c+2(b-a)t and x=a+t, y=b-t, z=c-2(b+a)t

Substitute (a,b,c) into z=y^2-x^2:
c=b^2-a^2
What are you proving here? That for ##t=0, x_0, y_0, z_0## are on the hyperbolic paraboloid? If so, you should say that. Or are you just stating what it means to say that (a,b,c) is on the hyperbolic paraboloid?
You should say something like: Since (a,b,c) is on the hyperbolic parabola, ##c=b^2-a^2##.
Fernando Rios said:
Substitute the parametric equations of L1 into the equation of the hyperbolic paraboloid in order to find points of intersection:
z=y^2-x^2
c+2(b-a)t=(b+t)^2-(a+t)^2=b^2-a^2+(b-a)t
Shouldn't this be ##b^2-a^2+2(b-a)t##?
Fernando Rios said:
c=b^2-a^2
You should state what this shows. (That x, y, z, satisfy the equation of the hyperbolic paraboloid for any value of t.)
 
Last edited:
  • #4
fresh_42 said:
Looks good, except that you should write it backward.

We need to show that all points ##\begin{bmatrix}
x\\y\\z \end{bmatrix}=\begin{bmatrix}a\\b\\c\end{bmatrix}+t\cdot \begin{bmatrix}
1\\ \pm 1\\ \pm 2b -2a\end{bmatrix}## obey the rule ##y^2-x^2=z.##
\begin{align*}
y^2-x^2&=(b\pm t)^2-(a+t)^2=b^2 \pm 2bt +t^2- a^2-2at-t^2\\
&=c + t(\pm 2b-2a)= c \pm 2(b\mp a)t=z
\end{align*}
Of course, you can handle both cases separately if you like that better.
Thank you for your answer.
 
  • #5
FactChecker said:
I think it looks good except that you should state more clearly what some steps are doing.

What are you proving here? That for ##t=0, x_0, y_0, z_0## are on the hyperbolic paraboloid? If so, you should say that. Or are you just stating what it means to say that (a,b,c) is on the hyperbolic paraboloid?
You should say something like: Since (a,b,c) is on the hyperbolic parabola, ##c=b^2-a^2##.

Shouldn't this be ##b^2-a^2+2(b-a)t##?

You should state what this shows. (That x, y, z, satisfy the equation of the hyperbolic paraboloid for any value of t.)
Thank you for your response.
 
  • #6
Alternative method:
Let [itex]f(x,y,z) = y^2 - x^2 - z[/itex]. Then [itex]r(t) = (A_x,A_y,A_z)t + (a, b, c)[/itex] lies entirely on the paraboloid if and only if [itex]f(r(t)) = 0[/itex]. We know this is the case when [itex]t = 0[/itex] (because we are given that [itex](a,b,c)[/itex] is on the surface), so we need [tex]
\begin{split}
0 &= \frac{df}{dt} \\ &= \frac{dr}{dt} \cdot (-2x(t), 2y(t), -1) \\
&= (A_x,A_y,A_z) \cdot (-2(A_xt + a), 2(A_yt + b), -1) \\
&= 2(A_y^2 - A_x^2)t + 2(bA_y - aA_x) - A_z
\end{split}[/tex] for all [itex]t[/itex]. This requires [itex]A_y^2 - A_x^2 = 0[/itex] and hence [tex]
(A_x,A_y,A_z) = A_x(1, \pm 1, 2(\pm b - a)).[/tex] Setting [itex]A_x = 1[/itex] gives the parametrizations specified in the question.
 
Back
Top